Analysis of rocuronium in human plasma by liquid chromatography-tandem mass spectrometry with application in clinical pharmacokinetics - Moraes, Natália Valadares de [UNESP]; Lauretti, Gabriela Rocha; Oliveira Filgueira, Gabriela Campos de; Portes Lopes, Bruno Carvalho; Lanchote, Vera Lucia (Elsevier B.V., 2014)
Rocuronium (ROC) is a neuromuscular blocking agent used in surgical procedures which is eliminated primarily by biliary excretion. A liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for analysis of ROC in human plasma. Separation of ROC and IS (verapamil) was performed using an endcapped C-18 column and a mixture of water:acetonitrile:trifluoracetic acid (50:50:0.1, v/v) as mobile phase. Aliquots of 100 mu L of human plasma were extracted at pH 3, using dichloromethane. The lower limit of quantification of 5 ng/mL shows the high sensitivity of this method. Intra- and inter-assay precision (as relative standard deviation) was all <= 14.2% and accuracy (as relative standard error) did not exceed 10.1%. The validated method was successfully applied to quantify ROC concentrations in patients under surgical procedures up to 6 h after the administration of the 0.4-0.9 mg/kg ROC. The pharmacokinetic parameter estimations of ROC showed AUC/dose of 563 mu g min/mL, total clearance of 2.5 mL/min/kg, volume of distribution at steady state of 190 mL/kg and mean residence time of 83 min. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Rocuronium; LC-MS/MS; Human plasma; Pharmacokinetics